The Plethora of Working Self Out: Relationship between Workload and Emotional Exhaustion among High School Teachers in Kiambu County, Kenya (Global Journal of Human-Social Science, 2022)
Less emotional exhaustion among teachers is critical in ensuring that teachers perform optimally in their various workloads However few studies have explored how various workloads for teachers can contribute to their emotional exhaustion The current study aimed to examine how various workload categories relate to emotional exhaustion among teachers in public high schools in Kiambu County Kenya The study adopted a descriptive survey design using a random sample of 367 participants drawn from 4447 teachers working in public high schools in Kiambu County at the time The quantitative data were collected using a workload questionnaire for assessing workload and the Maslach Burnout Inventory Scale MBI-S for burnout The qualitative data were collected using a structured interview guide and focus group discussions and descriptive frequency tables and percentages and inferential multinomial logistic regression statistics to analyze the data The study used Job Demand-Resource and Multidimensional theories to explain the relationship Results indicate a relationship between workload and emotional exhaustion among teachers in public high schools Emotional exhaustion can affect teachers physical mental emotional and social wellbeing The research recommends that school counselling departments be made comprehensive enough to accommodate workplace counselling to assist teachers deal with emotional exhaustion and acquiring overall mental health which would enhance their performance
Keywords: workload; burnout; public secondary schools; teachers; kiambu county